2018
DOI: 10.18203/issn.2455-4529.intjresdermatol20184463
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cases of dermatological referrals and their systemic correlation in a tertiary care hospital in Gangtok: a prospective study

Abstract: <p class="abstract"><strong>Background:</strong> Practice of dermatology in a teaching hospital is not merely limited to inpatient and out patients’ management but also boost up the clinical knowledge of young medical graduates and medical students. Many dermatological diseases might be directly or indirectly associated or related with the primary diseases for which the patient is admitted in the hospital or it may also be the dermatological manifestation of systemic diseases.</p><p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Among dermatological diagnosis, infections were the most common followed by eczema which was similar to other studies. 3,4,[10][11][12][13]17,[19][20][21][22][24][25][26] Viral infections were most common than fungal infections which was similar to the study by Sharma et al 19 Immunosuppression in admitted patients may be the reason for infections. Study by Fischer et al had candidiasis as the most common infection overall where as in present study it was the second common fungal infection next to dermatophyte.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Among dermatological diagnosis, infections were the most common followed by eczema which was similar to other studies. 3,4,[10][11][12][13]17,[19][20][21][22][24][25][26] Viral infections were most common than fungal infections which was similar to the study by Sharma et al 19 Immunosuppression in admitted patients may be the reason for infections. Study by Fischer et al had candidiasis as the most common infection overall where as in present study it was the second common fungal infection next to dermatophyte.…”
Section: Resultssupporting
confidence: 65%
“…This is in accordance with most of the available literature. 3,4,7,8,10,[12][13][14][15][16][17][18][19][20][21][22] Many medical disorders are associated with dermatological manifestations which serve as important clues for diagnosis of the underlying medical conditions. Other reasons include increased patient admissions in medicine, longer hospital stay, multiple diseases and polypharmacy thereby increasing the risk of adverse drug reaction and concurrent infections.…”
Section: Resultsmentioning
confidence: 99%
“…The ROC curve in our study had AUC value of 0.760 with the serum ferritin cutoff point for predicting mortality in sepsis patients of 975 ng/ml which a sensitivity of 87.5 %, specificity of 75 %, and p value of 0.006. Meanwhile Sharma et al study in childre with sepsis reported that elevated ferritin levels of > 1000 ng/L had a sensitivity of 58.9% and a specificity of 75.3% as a predictor of death with a relative risk of 2.38 (95% CI: 1.57-3.61) and an odds ratio of 4.36 ( 95% CI: 2.14 -8.88) while the AUC value was 0.68 (Sharma et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…In contrast to bacterial infection, it is usually associated with extensive over expression of IL-1β effecting an IL-6 to trigger hepatocytic CRP, which acts as an initial host defense by promoting bacterial phagocytosis. In addition, increased ferritin in sepsis can occur as a consequence blockade of iron release due to virulence factors induced by microorganisms in the acute phase (Sharma et al, 2018;Chiou et al, 2018;slats et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation